Percepção social e características do luto na viuvez - Lima, Mara Rúbia de Paula (2020)
The death of a partner follows secondary losses and can have a traumatic meaning for the mourner. Social support is a coping strategy in this process. The free expression of feelings is important for the mourning process. Objective: To understand the specific issues of mourning due to death according to the experience of widowers and their perceptions regarding society's reactions. Methods: Cross-sectional, descriptive research, with quantitative and qualitative analysis methods. Twelve (male and female) widowers have participated, partners of deceased patients in a hospital in the interior of São Paulo. An interview was used to characterize the sample, an in-depth interview and the application of the Prolonged Mourning Assessment Instrument PG-13. The protocol was carried out by telephone contact, recorded and transcribed in full. Data were analyzed quantitatively and qualitatively, with descriptive statistics and content analysis. Results: The sample was made up mostly of women (83%), with a mean age of 53.17 years, Catholic (58%), with incomplete elementary education (42%), with children (92%) and with dependents, experiencing grief at a mean period of 10.16 (8 to 14 months). The average age of the deceased partners was 57.67 years, the main cause of death was contamination by COVID-19 (67%), the importance attributed to the relationship received an average of 9.58 (0 for not at all important and 10 for too much important). Four categories emerged from the reports: intrapersonal reactions (perception of their reactions), interpersonal reactions (perception of social reactions), social support and prolonged mourning. The main intrapersonal reactions were disorganization and denial (at the time of the news), sadness and upset with the concreteness of death (during the burial ritual). Returning to work was pointed out as a coping strategy. At the time of the interview, mourning reactions varied according to the subjectivity of each process. As for interpersonal reactions, disbelief/denial and expressions of care and affection (at the time of the news) from society were described. Reactions of supporting and comfort are described soon after the loss, however, the scenario changes as the months was going by. At the time of the interview, most widowers avoided expressing their emotions in public, the reaction of encouragement and improvement proposed by society are described negatively. The majority has received support; family was most often mentioned, followed by friends and religion. They described themselves as partially or completely satisfied with the support. They left as guidelines for welcoming a mourner person: voluntary offer of supporting, respect and freedom to express grief. One participant presented a diagnosis for prolonged mourning according to the PG-13 instrument. Conclusion: Mourning in widowhood is a painful as well as a difficult experience to accept. Although some reactions are common at the initial moment of loss, throughout the process it develops according to the particularity of each subject. Social support is an important aid for a good development; however, the support network tends to withdraw or repress the mourner as the months of mourning are going by. Considering the universality of death and the resulting mourning; preparing the community for an adequate reception favors, in some way, everyone.